Hubungan Brand Equity Terhadap Keputusan Membeli Produk Pada Mahasiswa Universitas Yos Soedarso (Uniyos) - Hendro Rumpoko; Kartika Putri Larasati (Yos Soedarso Economic Journal (YEJ), 2020)
The main purpose of this research is to know the correlation between brand equity and decision in buying. According to Aaker (1997), brand equity have some impact by giving assets that have values to the customer, this value will increase customer’s self confidence to buy a product. The research participants are college student of Yos Soedarso University who are 18 – 25 years old, have pocket money ≤ Rp.200.000,- per month and also have understanding about branding. The measurement tools are questionaire that uses for measuring brand equity and decision in buying. The brand equity questionaire developed by using the dimensions of brand equity from Aaker (1997). Decision in buying questionaire developed by using the dimension of decision in buying  from  Engel (1995). The result shows that there is a positive correlation between brand equity and decision making (rxy = 0.514; p ≤ 0.05). This research need to be continued with different variabel such as the correlation between brand loyalty, brand awareness or perceived quality with decision in making. Different subject and some addition in tools are good to be considered. The implication of this research are giving some advantages for the company, marketing practitioner and also for the next researcher.------------Keyword: Brand Equity; Decision in Buying; Students.